Computational study of mortarless masonry system under axial loading - Mohd Bosro, Mohamad Zulhairi; Abdul Samad, Abdul Aziz; Mohamad, Noridah; Ali, Noorwirdawati; Inn, Goh Wan; Tambichik, Muhammad Afiq; Iman, Muhamad Afif (International Journal of Integrated Engineering, 2018)
Construction of building structure using the masonry block system has been around since a decade ago. Much of the ancient structures still standing strong today, proving that these construction systems are not badly swallowed by age. Presently, the development of the masonry block system was seen slowly with the increasing demand of quality and affordable housing. Taken Malaysia as an example, the newest of masonry systems developed is in the year 2004 with PUTRA block system developed by Universiti Putra Malaysia (UPM). With the advancement of Finite Element Analysis (FEA) software for designing and simulating process, the development of the masonry block system will be continued. Due to the heterogeneous and composite nature of masonry materials, its mechanical behavior is extremely complex to be applied in FEA study. Hence, material models were introduced and one of the possibilities is concrete damage plasticity (CDP) model offered in the ABAQUS/explicit software. The computational approach is by simulating the PUTRA block prism as the masonry system, consisting of two stretchers and the half block unit, without any mortar layers, represented by ABAQUS/explicit software conforming to CDP model constitutive laws. Findings from the study concluded that the global mesh size of 7 of C3D8R elements as the optimum meshing size for the PUTRA block model. The computational results show a good agreement with the experimental work where 98% accuracy level was achieved.